Acid-base free main group carbonyl analogues - Loh, YK; Aldridge, S (Wiley, 2020)
Main group carbonyl analogues (R2E=O) derived from p-block elements (E=groups 13 to 15) have long been considered as elusive species. Previously, employment of chemical tricks such as acid- and base-stabilization protocols granted access to these transient species in their masked forms. However, electronic and steric effects inevitably perturb their chemical reactivity and distinguish them from classical carbonyl compounds. A new era was marked by the recent isolation of acid–base free main group carbonyl analogues, ranging from a lighter boracarbonyl to the heavier silacarbonyls, phosphacarbonyls and a germacarbonyl. Most importantly, their unperturbed nature elicits exciting new chemistry, spanning the vista from classical organic carbonyl-type reactions to transition metal-like oxide ion transfer chemistry. In this Review, we survey the strategies used for the isolation of such systems and document their emerging reactivity profiles, with a view to providing fundamental comparisons both with carbon and transition metal oxo species. This highlights the emerging opportunities for exciting “crossover” reactivity offered by these derivatives of the p-block elements.